Evaluation Of The Health Education Program at The Ballaparang Public Health Center, Rappocini District Makassar City - Rahmi, Rahmi; Yunus, Muhammad; Zainal, Henni (Jurnal Administrasi Bisnis, 2026)
The purpose of this study was to determine the objectives of the Health education program, the success of the education program, and increase public knowledge regarding health issues through the education program at the Ballaparang Community Health Center. At the Ballaparang Community Health Center, online health education has been running for one year since 2024. The location of this research was at the Ballaparang Community Health Center, Rappocini District, Makassar City, taking into account that the Ballaparang Community Health Center has been conducting health education. The method used in this study is a qualitative method, meaning that the data collected are not in the form of numbers, but rather the data comes from the results of interviews, field notes, and documentation. The results of the research conducted at the Community Health Center are that the objectives of implementing the health education program at the Ballaparang Community Health Center have been quite achieved, seen from the community response to educational stories and the number of people who have watched health education material videos on the Community Health Center's social media. The health education program at the Community Health Center has also been quite successful, just as the program's objectives have been. This success has also had good results seen from the community who have participated in watching educational videos via the queue TV at the Ballaparang Community Health Center. Through the health education program at the Community Health Center, it has also provided additional knowledge to the community around the Ballaparang Community Health Center's work area, where the community has gained additional knowledge regarding diseases such as dengue fever, low blood pressure, and other diseases by watching health education videos at the Ballaparang Community Health Center both through social media and via the Community Health Center queue TV.